International Beta Genetic Resources Network: A report on the 4th International Beta Genetic Resources Workshop and World Beta Network Conference held at the Aegean Agricultural Research Institute, Izmir, Turkey, 28 February-3 March 1996 - Frese, L.; Panella, L.; Srivastava, H.M.; Lange, W.; International Plant Genetic Resources Institute (1996)
The World Beta Network (WBN) was founded in 1989 on the initiative of IPGRI. The goal of all crop-specific networks is to improve international collaboration between curators of collections and researchers and users of germplasm, and, through task-sharing, to enable maximum use of the often limited funds for conservation and utilization. The WBN needs to ensure the safest and most effective conservation methods of Beta germplasm and remember that the plant genetic resources should be accessible to those engaged in research, evaluation, crop improvement and use. The WBN reflects the desire of almost all countries in the world that are striving for collaboration and a joint sharing of the resulting benefits. Sharing of benefits would include joint research, access to new germplasm, access to technology, and access to information and training facilities, as well as sharing of financial profits. The network should continue to be instrumental in ensuring a share in the benefits arising from making plant genetic resources available to all.